Large-Slenderness-Ratio Supersonic Aircraft Lateral–Directional Coupling Dynamics Analysis and Control - Huitao Lyu; Zheng Gong; Yongliang Chen; Wanli Chen; Wenjian Wang (International Journal of Aerospace Engineering)
Large-slenderness-ratio aircraft in which a large portion of the aircraft’s mass is concentrated along its centreline face the problem of severe lateral-directional coupling. Previous research has not fully considered the inertia product when conducting stability analyses of such aircraft. However, neglecting the inertia product may threaten the safety of the aircraft during high-speed flight. This paper investigates the effect of the inertia product on the lateral–directional stability. Two methods, one based on eigenstructure assignment (EA) and the other based on an extended state observer (ESO), are developed for the lateral–directional decoupling of a research large-slenderness-ratio aircraft. Simulation results show that both methods can realize decoupling control. The EA-based control achieves better decoupling performance, whereas the ESO-based control has an advantage in terms of disturbance rejection. Finally, the ESO-based attitude controller is validated through a high subsonic flight test. The decoupling and tracking performance of the attitude control demonstrate the effectiveness and practicality of the ESO-based controller.